2011
DOI: 10.1159/000333825
|View full text |Cite
|
Sign up to set email alerts
|

HER3 Overexpression as an Independent Indicator of Poor Prognosis for Patients with Curatively Resected Pancreatic Cancer

Abstract: Objective: The association between human epidermal growth factor receptor 3 (HER3) overexpression and survival in patients with curatively resected pancreatic cancer was investigated. Methods: Tissue samples from 126 pancreatic cancers without hematogenous or peritoneal metastases recovered from macroscopically curative resection were fixed with formalin, embedded in paraffin and subjected to immunohistochemical staining. Semiquantitative scores of zero (no staining or staining in less than 10% of cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…Ferrone et al [20] reported that the preoperative level of CA19-9 was not an independent prognostic factor in patients with resectable pancreatic adenocarcinoma. However, a contradictory result has been revealed by the Waraya [10], Hartwig [22], and Hirakawa [15] groups, arguing that the preoperative CA19-9 level is an independent prognostic factor on multivariate analysis. The result from our study is consistent with the latter findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferrone et al [20] reported that the preoperative level of CA19-9 was not an independent prognostic factor in patients with resectable pancreatic adenocarcinoma. However, a contradictory result has been revealed by the Waraya [10], Hartwig [22], and Hirakawa [15] groups, arguing that the preoperative CA19-9 level is an independent prognostic factor on multivariate analysis. The result from our study is consistent with the latter findings.…”
Section: Discussionmentioning
confidence: 99%
“…Waraya et al [10] and Hirakawa et al [15] reported that a level of CA19-9 >37 was the independent prognostic factor. Berger et al [7] reported that undetectable preoperative CA19-9 levels and a value of CA19-9 >200 U/mL were related to survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HER3 is physiologically expressed in normal human tissues, such as the gastrointestinal, urinary, respiratory and reproductive tract and skin (2). In multiple cancer types, HER3 overexpression has been linked with poor prognosis which increased interest in HER3 as potential target in cancer therapy (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…HER protein staining was scored as either 0, 1+, 2+, or 3+, the cytoplasm and membrane-staining intensity and pattern were evaluated according to the following scale [20]: no staining is observed or is observed in less than 10% of the tumor cells (score 0), weak staining is detected in 10% or more tumor cells (score 1+), moderate staining is observed in 10% or more tumor cells (score 2+) and strong staining is observed in 10% or more tumor cells (score 3). Scores of 0, 1+ and 2+ were taken to represent negative protein expression, while a score of was 3+ was taken to represent positive protein expression.…”
Section: Methodsmentioning
confidence: 99%